Preparation of graphene oxide composited zinc oxide films by electrostatic spray deposition for humidity sensors - Thutiyaporn Thiwawong; Thitiwat Maboonchauy; Korakot Onlaor; Benchapol Tunhoo (Journal of Materials Science and Applied Energy, 2023)
This work aimed to study the preparation of graphene oxide (GO) and zinc oxide (ZnO) composited films by electrostatic spray deposition for use in fabricated humidity sensors. The physical properties of prepared films were examined with X-ray diffraction, Raman spectroscopy, and scanning electron microscope. Subsequently, a humidity sensor was fabricated using a low-cost interdigitated electrode pattern with the print circuit board. The humidity sensing behaviors were assessed with fixed humidity levels in a saturated aqueous salt solution in the humidity range of 11 – 93%RH. The impedance value of the device was obtained with a precision LCR meter. It was found that the composited film of 0.50 %wt. GO demonstrated the highest humidity response with optimized humidity sensitivity, hysteresis error, and response/recovery times of 2.68 ´ 103, 4.89%, and 228/19 s, respectively. Moreover, the equivalent circuits for the prepared device at various humidity levels were acquired with impedance spectroscopy to propose the mechanism for the humidity sensing of the device.
Keywords: Gas Sensing Nanomaterials and Sensors; Analytical Chemistry and Sensors; ZnO doping and properties